A comparison of alternative methods to construct confidence intervals for the estimate of a break date in linear regression models. (3rd July 2018) - Chang, Seong Yeon; Perron, Pierre
ABSTRACT: This article considers constructing confidence intervals for the date of a structural break in linear regression models. Using extensive simulations, we compare the performance of various procedures in terms of exact coverage rates and lengths of the confidence intervals. These include the procedures of Bai (1997 ) based on the asymptotic distribution under a shrinking shift framework, Elliott and Müller (2007 ) based on inverting a test locally invariant to the magnitude of break, Eo and Morley (2015 ) based on inverting a likelihood ratio test, and various bootstrap procedures. On the basis of achieving an exact coverage rate that is closest to the nominal level, Elliott and Müller's (2007 ) approach is by far the best one. However, this comes with a very high cost in terms of the length of the confidence intervals. When the errors are serially correlated and dealing with a change in intercept or a change in the coefficient of a stationary regressor with a high signal-to-noise ratio, the length of the confidence interval increases and approaches the whole sample as the magnitude of the change increases. The same problem occurs in models with a lagged dependent variable, a common case in practice. This drawback is not present for the other methods, which have similar properties. Theoretical results are provided to explain the drawbacks of Elliott and Müller's (2007 ) method.